Antipsychotic Polypharmacy and High-Dose Antipsychotic Regimens in the Residential Italian Forensic Psychiatric Population (REMS) - Mandarelli, Gabriele; Carabellese, Felice; Di Sciascio, Guido; Catanesi, Roberto (Frontiers in Psychology, 2022)
Few data exist regarding treatment with antipsychotics in forensic psychiatric patient populations with high social dangerousness. We performed a secondary analysis of 681 patients treated with at least one antipsychotic, extracted from a 1-year observational retrospective study, conducted on 730 patients treated in the Italian Residencies for Execution of Security Measures (REMS) (96.4% of the REMS population). We aimed at investigating antipsychotic polypharmacy (prescription of two or more concomitant antipsychotics) and high dose/very high-dose antipsychotics, as well as the possible factors associated with such therapeutic regimens. High dose/very high-dose antipsychotics were defined as a prescribed daily dose to WHO-defined daily dose ratio greater than 1.5 or 3.0, respectively. Binary logistic regression analysis was used in three models to test possible predictors of antipsychotic polypharmacy, high-dose antipsychotics, and very high-dose antipsychotic prescription. Antipsychotic polypharmacy resulted in n = 308 (45.2%) of the patients, n = 346 (50.8%) received high-dose antipsychotics, and n = 96 (14.1%) very high-dose antipsychotics. The multivariate analysis disclosed an association between antipsychotic polypharmacy and male gender (odds ratio (OR): 2.75 and 95% CI: 1.34–5.65), long-acting injectable (LAI) antipsychotic prescription (OR: 2.62 and 95% CI: 1.84–3.74), and aggressive behavior in REMS (OR: 1.63 and 95% CI: 1.13–2.36). High-dose antipsychotics were also associated with male gender (OR: 2.01 and 95% CI: 1.02–3.95), LAI antipsychotic prescription (OR: 2.78 and 95% CI: 1.95–3.97), and aggressive behavior in REMS (OR: 1.63 and 95% CI: 1.12–2.36). The use of antipsychotic polypharmacy and high-dose antipsychotics is frequent in the REMS population. These results might depend on regulatory and organizational aspects of the REMS system, including variability in structures, lack of a common model of care, and lack of stratified therapeutic security.